Intergenerational mobility and the timing of parental income - Pedro Carneiro; Italo Lopez Garcia; Kjell Salvanes; Emma Tominey (Centre for Microdata Methods and Practice (cemmap), 2015)
We extend the standard intergenerational mobility literature by modelling individual outcomes as a function of the whole history of parental income, using data from Norway. We find that, conditional on permanent income, education is maximized when income is balanced between the early childhood and middle childhood years. In addition, there is an advantage to having income occur in late adolescence rather than in early childhood. These result are consistent with a model of parental investments in children with multiple periods of childhood, income shocks, imperfect insurance, dynamic complementarity and uncertainty about the production function and the ability of the child.
Keywords: 330